Proposing Blockchain Technology Based Zakat Management Model to Enhance Muzakkis Trust in Zakat Agencies: A Conceptual Study - Zulfikri, Zulfikri; Hj Kassim, Salina; Hawariyuni, Weni (Journal of Accounting Research, Organization and Economics, 2021)
Objective This study proposes a conceptual framework of Zakat based management model using blockchain technology with its transparent, secure, auditable, and efficient system in order to enhance the trust in zakat agencies.Design/methodology This study is based on literature and theoretical reviews. This study took BAZNAS as the model of the Indonesian zakat agency to use Blockchain-based zakat payment on which zakat payers can track the fund allocated to the beneficiaries directly.Results This research demonstrates the importance of Blockchain and smart contract technologies in zakat management by developing a model that combines zakat management agencies with the components of Blockchain and smart contract technologies.Research limitations/implications The proposed model can contribute to the sustainability and efficiency of zakat agencies and is in line with the poverty eradication effort in Indonesia.